Optimization of COVID-19-Free Supply Chains - Pupavac, Drago; Maršanić, Robert; Krpan, Ljudevit (Promet - Traffic&Transportation, 2021)
The basic aim of this paper is to research the importance of supply chain optimization in the circumstances of the COVID-19 crisis. The research object is the optimum selection of active participants before and after the COVID-19 crisis. The initial hypothesis of this paper is that optimal COVID-19-free supply chains can be formed with a dynamic programming method, the costs of which will be higher than those when this restriction would not exist, but significantly lower than those formed if the optimization principle in the selection of supply chain stakeholders would be neglected. Research results in this scientific discussion paper are based on the analysis and synthesis method, comparative method, and dynamic programming method. The main findings of this paper point to the conclusion that the COVID-19 crisis affected the reduction of goods flow within supply chains, reduction of potential participants in supply chains, reduction of supply chains business safety, and increase in business costs.